Formation Study of the Copper(II) Complexes with Picolinic and Dipicolinic Acids in 1.0 mol.dm -3 KNO 3 at 25 °C - Ramos, Edwin; Hernández, Lino; Pérez, Alejandro; Madden, Waleska; Lubes, Vito (Rev. Téc. Fac. Ing. Univ. Zulia, 2017)
Ver Resumen PDF.